1.1: Invited Paper: Virtual Visor: Adding Intelligence to LCD Displays to Selectively Block Sunlight. (26th August 2021) - Zink, Jason; Todd, Ryan; Kumbar, Manjunath; Biyani, Arun; Huang, Xinyu; Ren, Liu
Abstract : A typical liquid crystal display (LCD) uses the liquid crystal to selectively modulate a constant backlight to produce an image for viewing. The Bosch Virtual Visor reuses this concept by employing a liquid crystal display as a sun visor to selectively block environmental light in an automotive setting. Instead of producing images for viewing, the Virtual Visor is designed to maximize a driver's ability to see the equivalent of its backlight — the scene in front of the driver. This requires perception and comprehension of the dynamic lighting conditions both inside and outside of the vehicle, and dynamic adaptation to each unique driver. The end result is a 90% improvement in visibility through the sun visor, dramatically improving driver visibility.